Definitive Molecular Level Characterization of Defects in UiO‐66 Crystals. (7th August 2015) - Trickett, Christopher A.; Gagnon, Kevin J.; Lee, Seungkyu; Gándara, Felipe; Bürgi, Hans‐Beat; Yaghi, Omar M.
Abstract The identification and characterization of defects, on the molecular level, in metal‐organic frameworks (MOFs) remain a challenge. With the extensive use of single‐crystal X‐ray diffraction (SXRD), the missing linker defects in the zirconium‐based MOF UiO‐66, Zr6O4(OH)4(C8H4O4)6, have been identified as water molecules coordinated directly to the zirconium centers. Charge balancing is achieved by hydroxide anions, which are hydrogen bonded within the pores of the framework. Furthermore, the precise nature of the defects and their concentration can be manipulated by altering the starting materials, synthesis conditions, and post‐synthetic modifications.